Photocatalytic Degradation of Phenol Using TiO2/Active Carbon - Daabool, Farah S.; Hussein, Falah H. (Asian Journal of Chemistry, 2015)
Photocatalytic degradation process was used to remove phenol from aqueous solution using pristine TiO2 and dipping TiO2 with activated carbon (AC). The 10 % AC/TiO2 was prepared by simple evaporation and drying process. Different techniques were used to characterize the prepared materials, such as Raman spectroscopy, scanning electron microscopy and X-ray diffraction. All the characterized methods show the real interaction between activated carbon and TiO2. The crystal sizes for prepared composite were calculated by using Scherrer equation from XRD data. The morphology of the prepared composite was studied using scanning electronic microscopy (SEM). From SEM image the particle size of the prepared materials was found to be equal 75 nm. The results show that 10 % of activated carbon was succeeding to increase the activity of TiO2 to 18 % towards photocatalytic degradation of phenol by TiO2.